Answer:
D. StartFraction negative 1 + StartRoot 3 EndRoot Over 2 EndFraction
Explanation:
Multiply numerator and denominator by the conjugate of the denominator. Then the denominator is the difference of squares, which will be rational. This simplification is called "rationalizing the denominator."
![(1)/(1+√(3))=(1)/(1+√(3))\cdot(1-√(3))/(1-√(3))=(1-√(3))/(1^2-(√(3))^2)\\\\=(1-√(3))/(-2)=\boxed{(-1+√(3))/(2)}](https://img.qammunity.org/2021/formulas/mathematics/college/wx9itkgt3aw0v0ts84r8l0gv0ap4vxpbe7.png)